IMPLEMENTING THE PHILOSOPHY OF 'SMOKOL TINUTUAN' AT MINAHASA FOR THE FORM OF EXCELLENT CHARACTER IN CHRISTIAN EDUCATION’S FRAMEWORK. - Saerang, Lodewyk Edward; Adrian, Tonny; Simanjuntak, Joksan; Pantury, Thomas; Rajaguguk, Wilson; Jura, Demsy (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This research explores Smokol Tinutuan as one of the habits of the Minahasa people and also as a philosophy embraced by Minahasa people who living in North Sulawesi Province. In their daily lives, the culture of smokol (breakfast) or shared breakfast is integral to the Minahasa people (in local language call Tou Minahasa), not only in North Sulawesi but also wherever the Minahasa people have migrated, even abroad. The culture of smokol together with Tinutuan has become like a ritual for the Minahasa people. Unbeknownst to many, Smokol Tinutuan contains a philosophy that is deeply embedded in the Minahasa person's character, promoting values such as gratitude and harmonious living together. From these two values, I have drawn parallels with the values of the Kingdom of Heaven in the Bible. The philosophy of Smokol Tinutuan can be seen in several Biblical stories about the character of strong leaders. If this philosophy is developed in Christian Religious Education, it can serve as a foundation to build excellent character and mentality, much like the leaders in the Bible, such as Daniel and his three friends in Babylon, as well as the disciples of Christ with Christ by the shores of the Sea of Galilee.